Complexity in Simplicity: Darel Carey on Op Art and the Responsive Eye - Ghida Djamil, Ben (Arte, Individuo y Sociedad, 2025)
This interview with visual artist Darel Carey explores his deep interest in optical perception and spatial illusions. He discusses how simple lines can generate complex planes and immersive environments, often producing a compelling sense of depth. He draws connections between op art and natural patterns, influenced by cosmology and psychology. Darel’s work epitomizes this movement, manipulating lines and space to challenge the viewer’s perception and create dynamic, shifting visual experiences. Through this dialogue, Darel provides insight into his artistic philosophy and the broader implications of his work for understanding perception and reality.